2020
DOI: 10.1016/j.jvolgeores.2019.106756
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of leachable elements in volcanic ashfall: a review and evaluation of a standardized protocol for ash hazard characterization

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 87 publications
(87 reference statements)
1
36
0
Order By: Relevance
“…Yet, compared to the other adsorbed hazards usually analysed on volcanic ash (e.g. potentially toxic elements such as As, Fe, Pb, F) (Stewart et al 2020), the presence of persistent organic pollutants on ash surfaces and their potential impact on the health hazard have been poorly investigated, to date. Only a limited number of studies have identified PCDD/Fs, PCBs and PAHs adsorbed onto volcanic ash, which were shown to originate from anthropogenic sources (Lamparski et al 1990;Takizawa et al 1994;Stracquadanio et al 2003;Guiñez et al 2020), but none has considered their in situ reactivity and the consequential impact of exposure to such particles on human (and environmental) health.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, compared to the other adsorbed hazards usually analysed on volcanic ash (e.g. potentially toxic elements such as As, Fe, Pb, F) (Stewart et al 2020), the presence of persistent organic pollutants on ash surfaces and their potential impact on the health hazard have been poorly investigated, to date. Only a limited number of studies have identified PCDD/Fs, PCBs and PAHs adsorbed onto volcanic ash, which were shown to originate from anthropogenic sources (Lamparski et al 1990;Takizawa et al 1994;Stracquadanio et al 2003;Guiñez et al 2020), but none has considered their in situ reactivity and the consequential impact of exposure to such particles on human (and environmental) health.…”
Section: Introductionmentioning
confidence: 99%
“…Acidified rainfall from persistent degassing can leach lead from plumbing fittings or roofing materials into roof catchment rainwater tanks (Macomber 2020). Ash deposition into water supplies can raise concentrations of fluoride and other potentially toxic elements (e.g., copper, manganese) as well as elements that impart an unpleasant taste or color to the water (Stewart et al 2006(Stewart et al , 2020.…”
Section: Volcanic Emission Hazardsmentioning
confidence: 99%
“…Leachate analyses can determine concentrations of readily soluble elements on fresh ash particles relevant to inhalation or ingestion pathways. These methods may require adaptation for ash from hydrothermal system eruptions which typically contain fluoride in slowly soluble forms (Cronin et al 2014;Stewart et al 2020). Ash can also scavenge biologically potent organic pollutants from the atmosphere (Tomašek et al 2021a).…”
Section: Hazard and Exposure Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Batch water leachate tests allow assessing environmental geochemical risks of ash fall, by examining the release of soluble ash compounds into the environment. Such releases can cause short-term though potentially significant impacts on the environment (Ruggieri et al, 2011;Stewart et al, 2020).…”
Section: Introductionmentioning
confidence: 99%